Adjustable acoustical performance based on deformable origamic shapes: a preliminary experimental investigation - Muarat, Nurul Farhanah (Trans Tech Publications Inc, 2014)
This paper describes a preliminary investigation on the possible use of deformable origamic shapes as a technique to provide adjustable acoustical performance in multi-purpose hall. The term ‘deformable’ means that the origamic shape undergoes deformation which automatically resulted into the change of its geometrical configurations. The experimental investigation has been carried out on three types of origamic shapes with several geometrical configurations. The measurement tests were conducted in a reverberation room and in accordance to ISO 354:2003 Measurement of Sound Absorption Coefficients in a Reverberation Room. Findings from the preliminary investigation show good trends indicating that the origamic shapes have the capability of adjusting the sound absorption coefficients by varying their geometrical configurations. Following those results, future works with details investigation will be undertaken as to validate the preliminary results.